2021
DOI: 10.47836/pjst.29.4.24
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Noise Pollution from Electric Backup Generators on the Operators’ Health

Abstract: Noise is a harmful pollutant that leads to an unsanitary environment in urban areas. Electric backup generators, widely used in developing countries, have been one of the most common noise sources. This study identifies workers’ public health in public electrical backup generators in Mosul City, Iraq. Workers’ health was assessed by measuring blood parameters, including Hb, RBCs, WBCs, PLT, and PCV. In addition, other biochemical parameters have been tested, such as; TP, ALB, F.B.S, Bilirubin, Blood Urea, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
(31 reference statements)
0
2
0
Order By: Relevance
“…According to [8], noise is a harmful pollutant that leads to an unsanitary environment in urban areas. This study identified workers' public health in a technological plant in Mosul City, Iraq.…”
Section: Introductionmentioning
confidence: 99%
“…According to [8], noise is a harmful pollutant that leads to an unsanitary environment in urban areas. This study identified workers' public health in a technological plant in Mosul City, Iraq.…”
Section: Introductionmentioning
confidence: 99%
“…Besides the thermal conditions, undesirable noise level (NL) has been recognised as an occupational hazard for various industries in developing and modern countries (Edelson et al, 2009;Mohammed & Rabeea, 2021). Noise annoyance and related issues in buildings were found to affect the emotions and productivity of the occupants (Lusk et al, 2009;Aalto et al, 2017).…”
Section: Introductionmentioning
confidence: 99%